Numerical Study to Investigate the Performance of U-shaped Flat Plate Solar Collector Using Phase Change Materials (PCMs) - Ibrahim Lazim Ihnayyish; Ahmed Qasim Ahmed; Abdulrahman Th. Mohammad; Ali Khalid Shaker Al-Syyab (Journal of Techniques)
Thermal solar collector considers one of the main devices employed to transform solar energy into thermal energy and can be classified into three main types named Evacuated tube collector (ETC), flat plate collector (FPC), and compound parabolic collector (CPC) collector. In this study, where it was taken to evacuated tube solar collectors three different geometries of the inner pipe diameter were proposed and combined with type of phase change materials (PCM) to evaluate their performance using PCM. And mass flow rate 0.5 L\min, A validated computational fluid dynamic (CFD) model was used in this examination. The data indicates that the highest outlet water temperature was observed at 45 ºC from 1:00 pm to 2:00 pm for case-1 with a smooth pipe, whereas for case-2 with two lobes and case-3 with four lobes, the maximum temperatures were 41 ºC and 40 ºC. respectively, The results showed that case-1 with Paraffin wax has the best efficiency among the proposed cases. Where it was recorded maximum outlet water temperature was about 45 ºC.